PRIORITY AREAS FOR THE DEVELOPMENT OF INVESTMENT POTENTIAL OF UZBEKISTAN - Abitovna, Khashimova Naima; Abdukadirovna, Buranova Manzura; Sagatovna, Abdurashidova Marina (International Journal of Psychosocial Rehabilitation, 2020)
The article considers the main directions of a long-term strategy of investment policy and the development of investment potential based on an action strategy in five priority areas of the country's economic development. Based on the strategic objectives of the country's economic development, the investment potential development strategy has been formulated and proposed. The conceptual foundations of the investment policy strategic objectives for the long term and the main directions of the investment potential development strategy based on the aggregate approach are proposed.